2022
DOI: 10.1111/mec.16709
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid‐derived weedy rice maintains adaptive combinations of alleles associated with seed dormancy

Abstract: Hybridization is a widespread phenomenon in plants and is a pathway for the evolution of adaptive traits. However, this process may also affect the persistence of combinations of adaptive alleles evolved through natural selection when hybridization occurs between adapted and non-adapted populations. Hybridization between weedy and cultivated rice has been confirmed with an adaptive introgression of deep seed dormancy alleles from cultivated rice. In this study, we explored the influence of hybridization on the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 81 publications
1
1
0
Order By: Relevance
“…In summary, the genome scan showed that aus-indica hybrid weeds can retain an optimal combination of traits and loci from both parents, which is in line with recent results of the stabilization of genomic regions associated with seed dormancy in hybrids between weedy and cultivated rice in Japan (Imaizumi et al, 2022).…”
Section: Signatures Of Adaptation In Argentinian Weedy Ricesupporting
confidence: 84%
“…In summary, the genome scan showed that aus-indica hybrid weeds can retain an optimal combination of traits and loci from both parents, which is in line with recent results of the stabilization of genomic regions associated with seed dormancy in hybrids between weedy and cultivated rice in Japan (Imaizumi et al, 2022).…”
Section: Signatures Of Adaptation In Argentinian Weedy Ricesupporting
confidence: 84%
“…In summary, the genome scan showed that aus-indica admixed weeds can retain an optimal combination of traits and loci from both parents, which is in line with recent results of the stabilization of genomic regions associated with seed dormancy in hybrids between weedy and cultivated rice in Japan (Imaizumi et al, 2022).…”
Section: Herbicide Resistance Helps To Understand the Origin Of Argen...supporting
confidence: 84%
“…As such, introgression is one of the driving forces for increasing genetic diversity and promoting adaptive evolution [3]. At present, many known gene introgression events involve adaptation [2], which is now known as adaptive introgression and has been found in plants [3,4], humans [5,6] and animals [7,8]. Hybridization is a method commonly used to breed new cultivars with desirable traits between wild and domesticated species in plant breeding [9,10].…”
Section: Introductionmentioning
confidence: 99%